Revisiting the ‘Slipper Slapper’ and other sculpture dedications in the clubhouse of the Poseidoniasts of Beirut - Martin, S. Rebecca (Journal of Greek Archaeology, 2017)
In 1904 a team led by French archaeologist Marcel Bulard discovered a sculptural group on the island of Delos in a building owned by businessmen from the Phoenician city of Beirut (Figures 1–6; Map 1). This work, now known as the ‘Sandal Slapper’ or ‘Slipper Slapper’, dates to c. 100 BCE. It shows Aphrodite holding up one of her sandals, Pan holding onto to her, and Aphrodite’s son Eros flying overhead. The group’s goddess is a quotation of the now-lost, late-Classical Aphrodite of Knidos by Praxiteles (fl. 364/361 BCE). In its preliminary publication, Bulard described the work: ‘Le groupe représente Aphrodite, se défendant avec l’aide d’Éros contre les entreprises de Pan.’ This interpretation of the group’s narrative – a bawdy scene in which Aphrodite brandishes her sandal at Pan’s sexual advances – is now standard.